STIK STROBERI: DIVERSIFIKASI PRODUK PANGAN, SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT KAMPUNG CIPARAY DESA INDRAGIRI - Zahra, Nur Adni Azkia; Hijaya, Andi; Faillah, Umi Lutfiatul; Fauzi, Ridho; Dwi Putra, Januar Hafiz; Rohdiana, Dadan (STAI Darul Qalam Tangerang, 2025)
Strawberries are a fruit with high nutritional value and significant economic potential. However, strawberry utilization by the Ciparay village community in Indragiri Village is still limited to selling fresh fruit to collectors, without further processing. Through the Community Service Program (KKN), students from Al Ghifari University, Bandung, initiated a community service activity in the form of an innovative strawberry processing product, strawberry sticks. This activity used a participatory approach, involving housewives and farmers as the primary target groups. The activity included planning, demonstrations, and evaluation through discussions and questions and answers. The results demonstrated high participant enthusiasm and a growing interest in developing the product independently. This program not only introduced a new food product but also provided practical skills that can support community economic development. This innovation is expected to expand the use of strawberries as a local commodity and support the development of businesses based on village potential.